Development and validation of an improved prediction model for vaginal birth after previous cesarean section: a retrospective cohort study of a Chinese population - Haiyan Liu; Yi Yu; Xiaoyue Zhang; Jiangnan Pei; Yao Tang; Rong Hu; Weirong Gu (Annals of Medicine)
Objective The transition from one-child to two-child and three-child policy in China has increasingly led to a rise in the number of women who choose trial of labor after cesarean section (TOLAC). Achieving vaginal birth after cesarean section (VBAC) is, however, not always guaranteed, and a failed TOLAC is associated with a high risk of maternal and neonatal complications. Although Grobman’s model may help predict VBAC, variations in population characteristics and healthcare settings can limit its generalizability and validity on a global scale. This study, therefore, seeks to develop and validate an improved prediction model for VBAC at the onset of labor among the Chinese population.Methods Seven hundred and twenty women who attempted a TOLAC were enrolled. The development dataset comprised 481 women, while the other 239 women constituted the temporal validation dataset. Variable selection was executed using the least absolute shrinkage and selection operator method. Model development was performed using logistic regression techniques and was presented as a nomogram.Results Of the participants, 81.4% achieved VBAC. The model included maternal age, maternal height, ratio of weight gain to pre-pregnancy weight, interval time of pregnancies, previous vaginal delivery, premature rupture of membranes, oxytocin administration, spontaneous labor onset, labor analgesia, and newborn weight. The development and temporally validated areas under the curve were 0.780 (95% confidence interval 0.726–0.834) and 0.774 (95% confidence interval 0.694–0.854), respectively. Internal validation performed by bootstrap resampling, calibration curves, and Hosmer-Lemeshow test confirmed the model’s robust performance. An optimal predicted probability cut-off of 0.7 was identified by decision curve analysis and clinical considerations.Conclusions The improved predictive VBAC model exhibited adequate performance such that women with a prior low transverse cesarean delivery who scored 0.7 or higher (in the model-derived probability score) would consider TOLAC, potentially leading to a reduction in maternal-neonatal morbidity.Registration The study was approved by the Ethical Committee of Obstetrics and Gynecology Hospital, Fudan University (2018-43) and was registered in the Chinese Clinical Trial Registry (ChiCTR1900022484), https://www.chictr.org.cn/showproj.html?proj=37898. The study adhered to the Declaration of Helsinki. The first participant was enrolled on January 1, 2016. The requirement for informed consent was waived because the data were anonymized.